RE-DESAIN FASILITAS KERJA KURSI ERGONOMI UNTUK MENGURANGI RISIKO MUSCULOSAL DISORDERS MENGACU PADA NILAI ANTROPOMETRI DI PT. X - Tri Widodo; Eko Setyawan (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2021)
PT. X is a company engaged in manufacturing with Radiator products. From the results of the Nordic Body Map in the production department of the press shop line section, many workers have complaints in the muscles (musculoskeletal disorders) because the workplace is not ergonomic as many as 15 workers, including aches in the neck of 3 people, back pain 4 people, back pain 1, stiff neck 5 people, bent body 2 people. From these results, there needs to be further action by making the design of the seatwork facility ergonomic concerning anthropometric values. With this reference, the design of popliteal height (TPo) 41 cm, popliteal buttocks (PPO) 39 cm, hip-width 38 cm, backrest height (TSP) 45 cm, seated back width (LSD) 35 cm, eye height sitting (TMD) 73 cm, height of backrest (TSP) 13 cm